Local Government Budget Management Strategies for Optimizing Regional Revenue - Krismiyati Krismiyati; Yesika Yanuarisa; Avid Leonardo Sari; Indra Kristian; Dadi Kuswandi (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
The presence of regional autonomy gives regional governments the authority to regulate their regional opinions. However, at the same time, regional development often results in a lack of ability of local governments to manage their budgets properly. This research then aims to look at how local governments manage their budgets to optimize Regional Revenue. This research was carried out using a descriptive qualitative approach. Â This research then found that regional budget management is the key to optimizing revenue. In overcoming central government dependency, efficient budget management is needed. Through monitoring, planning, and evaluation, the budget is maximized. A performance-based approach strengthens resource allocation and project assessment. Increasing regional income occurs through taxation, levies, community participation, and transparency. With good management, community involvement, and a focus on results, local governments achieve fiscal independence and local prosperity.